Modulation of urelumab glycosylation separates immune stimulatory activity from organ toxicity - Reitinger, Carmen; Ipsen Escobedo, Andrea; Hornung, Chiara; Heger, Lukas; Dudziak, Diana; Lux, Anja; Nimmerjahn, Falk (Frontiers in Immunology, 2022)
Checkpoint control and immunomodulatory antibodies have become important tools for modulating tumor or self-reactive immune responses. A major issue preventing to make full use of the potential of these immunomodulatory antibodies are the severe side-effects, ranging from systemic cytokine release syndrome to organ-specific toxicities. The IgG Fc-portion has been demonstrated to contribute to both, the desired as well as the undesired antibody activities of checkpoint control and immunomodulatory antibodies via binding to cellular Fcγ-receptors (FcγR). Thus, choosing IgG subclasses, such as human IgG4, with a low ability to interact with FcγRs has been identified as a potential strategy to limit FcγR or complement pathway dependent side-effects. However, even immunomodulatory antibodies on the human IgG4 background may interact with cellular FcγRs and show dose limiting toxicities. By using a humanized mouse model allowing to study the immunomodulatory activity of human checkpoint control antibodies in vivo, we demonstrate that deglycosylation of the CD137-specific IgG4 antibody urelumab results in an amelioration of liver toxicity, while maintaining T cell stimulatory activity. In addition, our results emphasize that antibody dosing impacts the separation of side-effects of urelumab from its therapeutic activity via IgG deglycosylation. Thus, glycoengineering of human IgG4 antibodies may be a possible approach to limit collateral damage by immunomodulatory antibodies and allow for a greater therapeutic window of opportunity.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD137; Fc-receptors; glycosylation; therapeutic antibody; urelumab

Tumor location determines tissue-specific recruitment of tumor-associated macrophages and antibody-dependent immunotherapy response - Lehmann, Birgit; Biburger, Markus; Brückner, Christin; Ipsen Escobedo, Andrea; Gordan, Sina; Lehmann, Christian; Vöhringer, David; Winkler, Thomas; Schaft, Niels; Dudziak, Diana; Sirbu, Horia; Nimmerjahn, Falk; et al. (Science immunology, 2017)
Despite recent advances in activating immune cells to target tumors, the presence of some immune cells, such as tumor-associated macrophages (TAMs) or tumor-associated neutrophils (TANs), may promote rather than inhibit tumor growth. However, it remains unclear how antibody-dependent tumor immunotherapies, such as cytotoxic or checkpoint control antibodies, affect different TAM or TAN populations, which abundantly express activating Fcγ receptors. In this study, we show that the tissue environment determines which cellular effector pathways are responsible for antibody-dependent tumor immunotherapy. Although TAMs derived from Ly6Chigh monocytes recruited by the CCL2-CCR2 axis were critical for tumor immunotherapy of skin tumors, the destruction of lung tumors was CCL2-independent and required the presence of colony-stimulating factor 2–dependent tissue-resident macrophages. Our findings suggest that TAMs may have a dual role not only in promoting tumor growth in certain tissue environments on the one hand but also in contributing to tumor cell destruction during antibody-mediated immunotherapy on the other hand.
EVALuna2:15237
Keywords: Cancer; Macrophages; Tumor associated macrophages; Antibodies; Tumor therapy; Immunotherapy